AN ERP STUDY ON EFFECTS OF COMPLEX MOTOR MOVEMENT TRAINING ON FOOTBALL PLAYERS' SUSTAINED ATTENTION PERFORMANCE - (:unkn) unknown (IEEE, 2015)
Complex motor movement exercises consist of a series of bodily exercises, and they are thought to be having positive effects on humans' cognitive abilities. The current study was conducted with football players to analyze these assumptions. Football players have trained with a series of bodily exercises for a month of period. Before and after the training, sustained attention and inhibition performances of experiment subjects and control group were assessed with a standard go/nogo task. The task was applied as both pre- and post-tests. Simultaneously with go/nogo task, EEG recordings with 16 channel were also taken. Thus, both behavioral and physiological assessments were able to be done. Results showed that training have improving effect on sustained attention and inhibition performances of subjects. Football players who had training showed higher performance on golnogo post-test than pre-test. On the other hand, football players who are not given any training did show no improvement on post-test. These results prove the assumption that complex motor exercises have improving effect on cognitive abilities, and they are also in concordance with literature.
Keywords: Complex Motor Movement Training; Causal relationship; Coherence; Football; INHIBITION